2020
DOI: 10.1590/scielopreprints.507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 e os impactos na saúde mental: uma amostra do Rio Grande do Sul

Abstract: As pandemias, como a de COVID-19, afetam uma quantidade relativamente grande de pessoas e impõem, pelo tempo que duram, novas regras e hábitos sociais para a população mundial. As informações sobre a pandemia são constantes na mídia. Além disso, o distanciamento social foi adotado também no Brasil como medida de prevenção da disseminação do novo coronavírus, o que pode ter consequências econômicas e psicossociais. Nesse contexto, o objetivo deste estudo foi verificar a associação entre o distanciamento social,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
60

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 0 publications
0
10
1
60
Order By: Relevance
“…However, people who reported being part of a risk group had less distress, contrary to findings of others [17,26]. Although this result could be spurious, alternatively, it could reflect a tendency of people who do not consider themselves be in major biological risk to feel more deprived in quarantine.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, people who reported being part of a risk group had less distress, contrary to findings of others [17,26]. Although this result could be spurious, alternatively, it could reflect a tendency of people who do not consider themselves be in major biological risk to feel more deprived in quarantine.…”
Section: Discussioncontrasting
confidence: 56%
“…One study [16] evaluated 88 nurses working in the pandemic health care and identified that a quarter of them had depression (25%) and almost half had signs of anxiety (48.9%). An online survey [17] carried out on a community sample of 799 participants from the state of Rio Grande do Sul identified that being female, younger, and the presence of previous disorders were predictors of mental disorder during the pandemic. In addition, it was observed that effects of the current context such as being in the risk group, losing income and being exposed to negative news increase the risks to mental health [17].…”
Section: Introductionmentioning
confidence: 99%
“…As diversas experiências da população diante da COVID-19 têm promovido o surgimento ou cronificação de problemas em saúde mental. Esse adoecimento coletivo em intensa escala gerou interferências negativas e significativas na vida das pessoas, tanto nos espaços domiciliares como no trabalho e escola/universidade (BARROS et al, 2020;DUARTE et al, 2020;FARO et al, 2020;SILVA, SANTOS, OLIVEIRA, 2020).…”
Section: Revisão Bibliográficaunclassified
“…No Brasil, o primeiro caso da doença foi notificado em 25 de fevereiro de 2020 (BRASIL, 2020), e o número de pessoas afetadas pelo vírus vem crescendo gradativamente desde então. Nesse sentido, considerando-se a falta de recursos ao enfrentamento da pandemia, causada por um agente desconhecido até então, a principal medida de prevenção da disseminação da COVID-19 consistiu no distanciamento social, exigindo isolamento domiciliar das pessoas (Duarte, Santos, Lima, Giordani & Trentini, 2020).…”
Section: Introductionunclassified